2020
DOI: 10.3390/plants9091059
|View full text |Cite
|
Sign up to set email alerts
|

Gaining Insight into Exclusive and Common Transcriptomic Features Linked to Drought and Salinity Responses across Fruit Tree Crops

Abstract: The present study aimed at identifying and mapping key genes expressed in root tissues involved in drought and salinity tolerance/resistance conserved among different fruit tree species. Twenty-six RNA-Seq samples were analyzed from six published studies in five plant species (Olea europaea, Vitis riparia Michx, Prunus mahaleb, Prunus persica, Phoenix dactylifera). This meta-analysis used a bioinformatic pipeline identifying 750 genes that were commonly modulated in three salinity studies and 683 genes that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Bioinformatic tools and techniques such as whole-genome sequencing and reference genomes have recently become readily available for the genus Prunus 24 26 . RNA-seq approach has been employed to study gene expression in response to drought and salinity in the roots of Prunus mahaleb and Prunus persica 27 . The dynamics of gene expression in leaves in response to alkaline stress has been reported in Prunus triloba Lindl 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic tools and techniques such as whole-genome sequencing and reference genomes have recently become readily available for the genus Prunus 24 26 . RNA-seq approach has been employed to study gene expression in response to drought and salinity in the roots of Prunus mahaleb and Prunus persica 27 . The dynamics of gene expression in leaves in response to alkaline stress has been reported in Prunus triloba Lindl 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it would be interesting to check if exogenous trehalose application can mitigate the phenomenon. The present work showed how “omic” studies could be effectively used to identify molecular gene regulatory networks occurring in plants involved in physiological responses to hormone dysregulation and environmental stresses such as previously found for other crops [ 59 , 60 , 61 ]. As concern cultivation practices, it is certainly necessary to prevent the tree from encountering biotic and abiotic stresses that can generally exacerbate the phenomenon, to set up proper irrigation and precision pruning practices to balance the sink/source equilibrium and to enhance photosynthesis, and to employ vigorous rootstock to ensure good water and carbohydrate resource status.…”
Section: Discussionmentioning
confidence: 55%
“…The aggregation of DEGs in molecular function was relatively concentrated, mainly in catalytic activity and binding. In addition, we found that a large number of DEGs were enriched in biological regulation (GO:0065007), antioxidant activity (GO:0016209), transcription regulator activity (GO:0140110), and transporter activity (GO:0005215), which are closely related to the plant response to drought stress [ 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%